2015
DOI: 10.1103/physreva.92.063601
|View full text |Cite
|
Sign up to set email alerts
|

Controllable nonlocal interactions between dark solitons in dipolar condensates

Abstract: We study the family of static and moving dark solitons in quasi-one-dimensional dipolar BoseEinstein condensates, exploring their modified form and interactions. The density dip of the soliton acts as a giant anti-dipole which adds a non-local contribution to the conventional local solitonsoliton interaction. We map out the stability diagram as a function of the strength and polarization direction of the atomic dipoles, identifying both roton and phonon instabilities. Away from these instabilities, the soliton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 71 publications
1
41
0
Order By: Relevance
“…several individual solitons forming bound objects) and also breathers, which are single solitonic entities that can be thought of as excited states of the focussing nonlinear Schrödinger equation, which have recently been engineered experimentally with matter waves for the first time [70] using an attractive gas of 85 Rb. Soliton molecules have been studied in various guises within the context of ultracold matter, for example the realization of degeneracy with atomic species possessing significant dipole-dipole interactions has led to the prediction of novel molecular states in these systems [71][72][73]. Related to this are the realisation of 'droplets' of both dipolar matter [74][75][76] and intriguingly, also light with a non-trivial angular momentum structure [77], as well as the prediction of soliton molecules in systems with nonlocal interactions [78].…”
Section: Soliton Molecules 41 Soliton Trimersmentioning
confidence: 99%
“…several individual solitons forming bound objects) and also breathers, which are single solitonic entities that can be thought of as excited states of the focussing nonlinear Schrödinger equation, which have recently been engineered experimentally with matter waves for the first time [70] using an attractive gas of 85 Rb. Soliton molecules have been studied in various guises within the context of ultracold matter, for example the realization of degeneracy with atomic species possessing significant dipole-dipole interactions has led to the prediction of novel molecular states in these systems [71][72][73]. Related to this are the realisation of 'droplets' of both dipolar matter [74][75][76] and intriguingly, also light with a non-trivial angular momentum structure [77], as well as the prediction of soliton molecules in systems with nonlocal interactions [78].…”
Section: Soliton Molecules 41 Soliton Trimersmentioning
confidence: 99%
“…For purely dipolar (g = 0), oblate condensates, Wilson et al [120,122] numerically found vortex ripples for moderate trap ratios 17 γ ∼ , see figure 7 (top) [120], and established the link to roton mixing into the vortex solution, similar to the biconcave structure that they found was induced in vortex-free dipolar condensates (energetic favourability of dipoles aligning head-to-tail). Vortex ripples have since been studied in other works [123,129,134], and similar ripples arise in the presence of other localized density depletions, such as due to localized repulsive potentials [122,130] and dark solitons [149,150]. The presence of the vortex slightly reduces the stable parameter space for the condensate relative to the vortex-free condensate [120,144].…”
Section: General Features Of a Vortex In A Quantum Ferrofluidmentioning
confidence: 99%
“…Thus, in the rapid-rotation limit, the tilt angle ϕ may be used to tune the effective strength of the DDI and in particular, when cos 2 ϕ > 1 3, the effective DDI strength becomes negative, corresponding to an unusual 'antidipolar' regime in which side-by-side alignment of the dipole moments is energetically preferred to head-to-tail alignments. Subsequent theoretical studies of dipolar BECs in this regime, which invoked the rotational tuning mechanism by setting C dd < 0, led to predictions of novel physics such as molecular bound states in dark solitons [24], multi-dimensional dark [25] and bright [26,27] solitons, stratified turbulence [28] and the roton instability of vortex lines [29]. In this direction, a recent experimental study of rotational tuning by Tang et al [30] has reported a realization of the anti-dipolar regime.…”
mentioning
confidence: 99%